2017
DOI: 10.1007/s00167-017-4548-0
|View full text |Cite
|
Sign up to set email alerts
|

Patella height is not altered by descending medial open-wedge high tibial osteotomy (HTO) compared to ascending HTO

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 65 publications
5
65
1
4
Order By: Relevance
“…16,19 Recently, OWHTO below the tibial tuberosity has aroused attention and shown significant improvements in radiographic parameters and knee function without changes in patellar height or PTS. [22][23][24][25][26] An early study reported that this technique could lead to the potential for fracture of the tibial tubercle fragment. 45 Park et al also observed two tibial tuberosity fractures with this technique, and they noted that this condition is easily preventable with caution (i.e., leaving at least a 1 cm thickness on the proximal tuberosity fragment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19 Recently, OWHTO below the tibial tuberosity has aroused attention and shown significant improvements in radiographic parameters and knee function without changes in patellar height or PTS. [22][23][24][25][26] An early study reported that this technique could lead to the potential for fracture of the tibial tubercle fragment. 45 Park et al also observed two tibial tuberosity fractures with this technique, and they noted that this condition is easily preventable with caution (i.e., leaving at least a 1 cm thickness on the proximal tuberosity fragment).…”
Section: Discussionmentioning
confidence: 99%
“…17 Different surgical techniques also have different influences on patellar height, with some studies suggesting that OWHTO below the tibial tubercle does not affect patellar height. [22][23][24][25][26] Some studies also suggested that patellar height decreases significantly if the knee axis correction is greater than 15 degrees after OWHTO, and patellar tracking will also be seriously affected if the correction of knee axis exceeds 15 degrees. 14,27 Although many studies have reported a change in patellar position after OWHTO, most of these studies used the measurements based on tibial reference, and these measurements should not be relied upon in surgical procedure involving the proximal tibia.…”
mentioning
confidence: 99%
“…To prevent patellar infera, some studies [10,11,20,21] have suggested that modified biplanar OWHTO is performed. In cases in which a separate descending osteotomy is performed by leaving the tuberosity attached to the proximal tibia, the patella height is not influenced, preventing the progression of patellofemoral joint OA.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent patellar infra, some studies [10,11,20,21] have suggested that modi ed biplanar OWHTO is performed. In cases in which a separate descending osteotomy is performed by leaving the tuberosity attached to the proximal tibia, the patella height is not in uenced, preventing the progression of patellofemoral joint OA.…”
Section: Discussionmentioning
confidence: 99%